THE STYLISTIC FEATURES OF DIVINE PROMISES TO BELIEVERS IN SURAH MUHAMMAD: AN ARABIC STYLISTICS STUDY: GAYA BAHASA JANJI ALLAH KEPADA ORANG BERIMAN DALAM SURAH MUHAMMAD (STUDI STILISTIKA ARAB) - Muslimatuz Zahro’; Mirwan Akhmad Taufiq; Atiq Mohammad Romdlon (ALLAIS Journal of Arabic Language and Literature, 2025)
This study aims to examine the stylistic features employed in conveying divine promises to believers in Surah Muhammad, as well as the linguistic patterns manifested in its verses. The research adopts a qualitative descriptive method with a stylistic approach, focusing specifically on verses that articulate divine promises. The data were collected through close reading and note-taking techniques and subsequently analyzed using linguistic theories encompassing phonology, morphology, syntax, and semantics. The findings indicate that: (1) the dominance of the consonantal sounds lām, mīm, and nūn carries particular stylistic significance, functioning as central phonological elements closely related to the contextual framework of Surah Muhammad. The articulation of divine promises to believers is frequently introduced through oath-based constructions. (2) The use of fiʿl māḍī and fiʿl muḍāriʿ reflects the continuous and enduring nature of divine promises, which apply both in worldly life and in the hereafter. (3) The employment of emphatic structures (tawkīd) and prohibitive expressions serves to reinforce the magnitude and certainty of these promises. (4) The selection of polysemous diction contributes to semantic depth and allows for broader interpretative understanding of the messages conveyed in the verses.